(untitled) (World Bulletin of Public Health, 2023)
Obesity is one of the most socially significant chronic diseases, which has assumed epidemic proportions, while obesity in pregnant women is attracting increasing attention. Despite constant improvements in the system antenatal care and obstetric care, the number of pregnant women with obesity is constantly increasing, and therefore the relevance of this issue is of particular importance. The review highlights the main mechanisms for the development of obesity and hormonal disorders during pregnancy, the risks and complications associated with obesity during pregnancy. Measures outlined prevention of overweight before and during pregnancy. Key words: obesity, pregnancy, insulin resistance, gestational diabetes.